Teori Niat Dan Ungkapan Dalam Qawaid Fiqhiyah Dan Penerapannya Dalam Fiqh - Fauzi, Anwar; Masdukhin, Arif (ASAS, 2023)
It is undeniable that the social changes faced by Muslims from generation to generation until now have invited various new problems or problems that require the establishment of Islamic law. And in this determination of Islamic law it is a necessity in accordance with the principles of Islamic law which are always relevant to the changes and developments of the times. Therefore, ijtihad is needed in solving and seeking legal solutions to community legal problems. So that the resulting ijtihad product is a legal product that is needed to answer various new problems that arise at this time. And in the process of carrying out ijtihad, of course, a legal istinbath methodology is needed, one of which is the al-Qawa'id al-Fiqhiyyah method or fiqh rules and here the author tries to study the theory of intention and how it applies to problems in fiqh in the field of muamalah. by using research that is library research. Where the discussion in this paper is based on literature related to the theory of intention in qawaid fiqhiyah and its application in muamalah fiqh. So that this discussion can provide a complete picture regarding the concept of intention theory and its application in muamalah.Keywords: Islamic law, intention, qaidah fiqhiyah